The call of classical literature in the romantic age - Van Anglen, Kevin P.; Engell, James, 1951- (Edinburgh University Press, 2017)
The Call of Classical Literature in the Romantic Age reveals the extent to which writers now called romantic venerate and use classical texts to transform lyric and narrative poetry, the novel, mythology, politics, and issues of race and slavery, as well as to provide models for their own literary careers and personal lives.